Dielectric relaxation and charge carrier mechanism in doped Ce1-xSmxO2-δ (0 ≤ x ≤ 0.3) nanoceramics: An investigation with dielectric spectroscopy. (May 2023) - Nath, Chandrani; Bharti, Purnima; Kumar, Sanjeet; Singh, Satyendra
Abstract: We present herein the structural, dielectric, and ionic conduction properties of a series of doped Ce1- x Sm x O2-δ (0 ≤  x  ≤ 0.3) nanocrystalline ceramics. X-ray photoelectron spectroscopy studies have indicated a non-stoichiometry induced mixed Ce 4+ and Ce 3+ charge state, with the content of Ce 3+ ions decreasing with increasing Sm concentration. Analysis of impedance data has suggested that both grains and grain boundaries contribute to the overall conductivity, but grain boundaries make the dominant contribution. Further, we have observed an enhancement in conductivity, which can be attributed to reduced grain size and increased interfaces in these nanostructured materials that lead to faster ionic diffusion across the boundaries. While our results suggest that dopant vacancy related high frequency relaxation is active in all the materials, for the sample with x  = 0.2 we have found two Debye-type dipoles in the relaxation process, with an additional low frequency dipole relaxation due to long-range migration of free oxygen vacancies. This migration is responsible for high conductivity in Ce0.8 Sm0.2 O2-δ, making the compound an ideal candidate for applications. Highlights: The mechanism of dielectric relaxation and conductivity of Sm doped nanoceria (Ce1-x Smx O2-δ ) are investigated using Debye theory. The nanostructuring of ceria significantly decreases the grain boundary resistance. The total conductivity of x = 0.2 doped ceria reaches 0.02 S/cm at 500 °C, an order higher than other reported values. The x = 0.2 sample exhibits two Debye type relaxations attributed to long range migration of VO ●● and dopant-vacancy associate (SmCe ' - VO . ●● ).